ENHANCING CRITICAL THINKING IN FIQH LEARNING: THE ROLE OF STRATEGIES AND MEDIA INTEGRATION IN ISLAMIC HIGHER EDUCATION (Malaysian Journal of Learning and Instruction, 2025)
Purpose – Fiqh learning has traditionally focused on cognitive aspects, such as recalling concepts or matching problems with answers in classical texts. Consequently, it has often neglected the cultivation of learners' critical thinking skills. This study aims to analyze students’ critical thinking practices in fiqh learning, explore the instructional strategies employed, and identify the types of technology used in fiqh learning activities. Additionally, it investigates the continuity between critical thinking, learning strategies, and technology in the context of fiqh education.Methodology – A mixed methods approach was adopted, using an explanatory sequential design. The study began with quantitative data collection and analysis, followed by qualitative exploration. A total of 254 students from eight universities in East Java, Indonesia, participated in the study. Quantitative data were collected through online questionnaires and analyzed using descriptive statistics, correlation analysis, and tests of difference. Qualitative data were gathered through observations and interviews and analyzed through data condensation, presentation, and conclusion drawing.Findings – The results indicate that students’ critical thinking practices in fiqh learning are generally neutral and somewhat inconsistent. Problem-based learning (PBL) and research-based learning (RBL) emerged as the most frequently applied strategies, with PBL noted as particularly effective in fostering critical thinking. The study highlights that these strategies are most effective when supported by various forms of instructional media. The integration of contextual learning strategies with multimedia use enhances students’ critical thinking engagement in fiqh learning.Significance – This study provides practical insights for lecturers in selecting appropriate learning strategies and media to promote critical thinking in fiqh education. While RBL and PBL strategies, supported by multimedia, show strong potential to enhance critical thinking, they are not definitive solutions. Effective strategies and media should be tailored to the characteristics and needs of students. Continued development of both RBL and PBL strategies and multimedia use is essential. Ultimately, fiqh learning in higher education should employ instructional approaches that enhance deeper understanding and critical engagement with the subject matter.